1998
DOI: 10.1063/1.872791
|View full text |Cite
|
Sign up to set email alerts
|

Linear and nonlinear particle-magnetohydrodynamic simulations of the toroidal Alfvén eigenmode

Abstract: Linear and nonlinear particle-magnetohydrodynamic ͑MHD͒ simulation codes are developed to study interactions between energetic ions and MHD modes. Energetic alpha particles with the slowing-down distribution are considered and the behavior of nϭ2 toroidal Alfvén eigenmodes ͑TAE modes͒ is investigated with the parameters pertinent to the present large tokamaks. The linear simulation reveals the resonance condition between alpha particles and TAE mode. In the nonlinear simulation, two nϭ2 TAE modes are destabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
204
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 160 publications
(217 citation statements)
references
References 14 publications
4
204
0
1
Order By: Relevance
“…Appel et al [50] found appreciable diffusion of super-Alfvénic alphas when the TAE or kinetic TAE amplitude was 4×10 −3 . In simulations of a global TAE, Todo and Sato [51] found appreciable alpha particle transport for mode amplitudes similar to Sigmar et al In the simulations of Candy et al [52], a single dominant TAE grew to a very large amplitude of B r /B 0 > 10 −2 . In simulations of beamion transport, Carolipio et al computed losses of a few percent for global TAEs at an amplitude of B r /B 0 = 4 × 10 −3 .…”
Section: Discussionmentioning
confidence: 89%
“…Appel et al [50] found appreciable diffusion of super-Alfvénic alphas when the TAE or kinetic TAE amplitude was 4×10 −3 . In simulations of a global TAE, Todo and Sato [51] found appreciable alpha particle transport for mode amplitudes similar to Sigmar et al In the simulations of Candy et al [52], a single dominant TAE grew to a very large amplitude of B r /B 0 > 10 −2 . In simulations of beamion transport, Carolipio et al computed losses of a few percent for global TAEs at an amplitude of B r /B 0 = 4 × 10 −3 .…”
Section: Discussionmentioning
confidence: 89%
“…8 We reported that there is an unstable mode near the plasma center and frequency sweeping close to that of the fast FS mode takes place. 9 The ratio of the linear damping rate ␥ d to the linear growth rate ␥ L in the simulation is consistent with hole-clump pair creation which takes place when ␥ d / ␥ L is greater than 0.4.…”
Section: Introductionmentioning
confidence: 99%
“…(2) is just a scalar pressure gradient in the same form as the bulk pressure gradient. 8 Then, the equilibrium can be obtained from the GradShafranov equation neglecting the energetic-ion orbit width. However, if the energetic-ion pressure is anisotropic in the velocity space and/or the energetic-ion orbit width is not negligibly small, the Grad-Shafranov equation should be extended.…”
Section: ͑16͒mentioning
confidence: 99%
See 2 more Smart Citations